Protocol for a randomised, open-label, parallel group, multicentre controlled study to evaluate the clinical performance and safety of Stay Safe Link compared with Stay Safe in patients with end-stage kidney disease on continuous ambulatory peritoneal dialysis. Issue 3 (8th March 2019) - Mak, Wen Yao; Ong, Loke Meng; Goh, Bak Leong; Bavanandan, Sunita; Mushahar, Lily; Leong, Chin Tho; Hooi, Lai Seong
Abstract : Introduction: Peritonitis is a major complication of continuous ambulatory peritoneal dialysis (CAPD), the risk of which is significantly influenced by the type of PD transfer system. Although the Y-disconnect and double-bag system is more efficient in preventing peritonitis compared with the spike system, little information is available to differentiate risks between different brands of the Y-disconnect double-bag system. A randomised controlled trial to evaluate the safety and efficacy of a newly introduced system is needed to provide the necessary clinical evidence to guide policy decision-making. Methods and analysis: The study is an open-label randomised controlled trial. A total of 434 patients with end-stage renal disease undergoing CAPD will be enrolled and randomised to either the intervention group, Stay Safe Link, or the control group, Stay Safe. All study subjects will be followed up and monitored for 1 year. The primary safety outcome is the rate of peritonitis while the primary efficacy outcomes are the delivered dialysis dose and ultrafiltration volume. Ethics and dissemination: The study was approved by the Medical Research Ethics Committee, National Institute of Health Malaysia. A written informed consent will be obtained from all participating subjects prior to any trial-related procedure and the study conduct will adhere strictly to Good Clinical Practice. The findings will be disseminated in a peer-reviewed journal. Trial registration number: NCT03177031; Pre-results.